Sea Defence Project and a UNESCO World Heritage Monument in Coastal Ghana - Justice Mensah (Advances in Civil Engineering)
Coastal erosion, sand and gravel mining, and open defecation threaten the sustainability and outstanding universal value (OUV) of heritage monuments dotted along the coast of Ghana. A sea defence project has been embarked upon in some areas in Ghana to, among other reasons, safeguard coastal resources, including the historic heritage monuments—castles and forts. This study examined the implications of the project for the sustainability and OUV of a UNESCO World Heritage Site (WHS) along the Ghanaian coastline. The study used a qualitative research design. In-depth interviews and focus group discussions were conducted to collect data from key stakeholders and analyzed using the thematic method. It became evident that the project has helped reduce oceanic effects, sand and gravel mining hazards, and open defecation in the direct neighbourhood of the site. These have increased the resilience and protective capacity of the monument and enhanced the aesthetic value and sanitation at the site, thereby shoring up the integrity and authenticity of the site and culminating in its enhanced sustainability and OUV. UNESCO, the State Party, Ghana Museums and Monuments Board, Municipal Authority, and Community Leaders should ensure that the advantages that have accrued to the site from the sea defence project are safeguarded and maximized. Additionally, the project should be extended to other coastal areas in the country where similar monuments are located to enable those monuments to derive similar benefits for sustainable development. The study contributes to understanding the protective and aesthetic nexus between coastal engineering and sustainable coastal heritage management.